Feed palatability and consumption of Eclectus Roratus Biaki in The Captivity of Bird and Ochid Park in Biak Numfor - Kafiar, Apner Penehas; Suawa, Elfira Kariane; Saragih, Evi Warintan (Fakultas Peternakan Universitas Papua, 2024)
This study aimed to assess the palatability and feed consumption of bayan parrots (Eclectus roratus biaki) in the captivity at the Bird and Orchid Park in Biak, using a variety of local feed combinations. The feeds consisted of fruits (papaya and bananas) and seeds (mung beans and sweet corn). A total of 8 parrots (4 males and four females) were used, housed in pairs within individual cages. Four treatments were tested: P0 (papaya and banana), P1 (papaya, banana, and mung beans), P2 (papaya, banana, and sweet corn), and P3 (papaya, banana, mung beans, and sweet corn). Feed and water were provided ad libitum and feed consumption was measured by weighing the remaining feed daily. The results indicated that bananas had the highest palatability and consumption across all treatments, with the highest feed consumption occurring in the P3 treatment, which included a combination of fruits and seeds. Palatability index, dry matter intake, and organic matter intake were higher when parrots were offered a varied diet. No significant differences were found between treatments in daily consumption, but the variety in feed combinations led to improved consumption patterns. The findings suggest that providing a balanced and varied diet consisting of fruits and seeds is crucial for optimizing bayan parrots' nutritional intake and health in captivity. This study contributes to improved feeding strategies for captive management and conservation efforts, ensuring the well-being of this endemic species.